The Role of Vitamin D3 in Improving Lipid Profile in Type 2 Diabetes Patients with Cardio Vascular Disease - Yassamen Samer Abd Aon; Sanaa Jasim Kadhim; Inas Hassan Mohammed Al Khafaji; Noor Thiar Tahir (Indian Journal of Forensic Medicine & Toxicology, 2022)
Hyperglycemia is the major risk factor for microvascular complications in patients with type 2 diabetes (T2D). Vitamin D a fat-soluble prohormone, has wide-ranging roles in the regulation of many physiological processes through their interactions with. This aim of this study to investigate the role of Vitamin D3 and other biochemical to associated with the risk of type 2 diabetes with CVD. This study was carried out at the National Diabetes Center (NDC) / Mustansiriyah University during the period from 1/11/2020 to 1/2/2021. group of type2 diabetes with CVD patients, including 80 patients from both sexes (male and female), and apparently healthy control group (n=40) were enrolled. The highest significantly were in values of FBS , HbA1c, TC , TG , LDL) were (195.33 - 89.45 mg/dl, P= 0.001; 8.75 - 4.86 %, P= 0.001; 234.08 158.9 mg/dl, P= 0.001, 221.25 versus 83.37 mg/dl, P= 0.001 and 132.62 - 87.40 mg/dl, P= 0.001 respectively). Vitamin D3 levels were significantly lower for patients group than that in control healthy people were. The conclusion of this study found Vitamin D3 Deficiency showed effective on lipid profile in Type2 diabetes patients with CVD .